2011
DOI: 10.1016/j.neuropharm.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological elevation of anandamide impairs short-term memory by altering the neurophysiology in the hippocampus

Abstract: In rodents, many exogenous cannabinoid agonists including Δ9-THC and WIN 55,212-2 (WIN-2) have been shown to impair short-term memory (STM) by inhibition of hippocampal neuronal assemblies. However, the mechanisms by which endocannabinoids such as anandamide and 2-arachidonylglycerol (2-AG) modulate STM processes are not well understood. Here the effects of anandamide on performance of a Delayed Non-Match to Sample (DNMS) task (i.e., STM task) and concomitant hippocampal ensemble activity were assessed followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 67 publications
1
18
1
Order By: Relevance
“…Their behavioral procedure is sensitive to impairment by THC, and these impairments correlate with suppressed hippocampal cell firing around the time of the sample response, presumably representing disrupted encoding of the sample (Hampson and Deadwyler 2000). Goonawardena et al (2011) found that treatment with methanandamide or URB597 (3 mg/kg) produced THC-like effects on memory and hippocampal cell firing. It is unclear why URB597 produced impairments in their procedure but not ours, but one possibility is the use of Long-Evans rats in their study versus Sprague-Dawley rats in ours.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Their behavioral procedure is sensitive to impairment by THC, and these impairments correlate with suppressed hippocampal cell firing around the time of the sample response, presumably representing disrupted encoding of the sample (Hampson and Deadwyler 2000). Goonawardena et al (2011) found that treatment with methanandamide or URB597 (3 mg/kg) produced THC-like effects on memory and hippocampal cell firing. It is unclear why URB597 produced impairments in their procedure but not ours, but one possibility is the use of Long-Evans rats in their study versus Sprague-Dawley rats in ours.…”
Section: Discussionmentioning
confidence: 93%
“…Goonawardena et al (2011) used a delayed nonmatching-to-position procedure that was similar to the one used in the present study, but used retractable levers instead of lighted nosepoke holes to present the samples and record the responses. Their behavioral procedure is sensitive to impairment by THC, and these impairments correlate with suppressed hippocampal cell firing around the time of the sample response, presumably representing disrupted encoding of the sample (Hampson and Deadwyler 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pertains not only to short-term memory (Goonawardena et al , 2010a, 2010b, 2011a, 2011b) but also to the consolidation process underlying long-term memory formation (Clarke et al , 2008; Robinson et al , 2008, 2010). Memory consolidation, however, is critically dependent on the occurrence of regular sleep patterns (Brankack et al , 2009; Platt and Riedel, 2011).…”
Section: Introductionmentioning
confidence: 99%